Coevolution of head, neck, and tail domains of myosin heavy chains - Korn, Edward D. (The National Academy of Sciences, 2000)
Myosins, a large family of actin-based motors, have one or two heavy chains with one or more light chains associated with each heavy chain. The heavy chains have a (generally) N-terminal head domain with an ATPase and actin-binding site, followed by a neck domain to which the light chains bind, and a C-terminal tail domain through which the heavy chains self-associate and/or bind the myosin to its cargo. Approximately 140 members of the myosin superfamily have been grouped into 17 classes based on the sequences of their head domains. I now show that a phylogenetic tree based on the sequences of the combined neck and tail domains groups 144 myosins, with a few exceptions, into the same 17 classes. For the nine myosin classes that have multiple members, phylogenetic trees based on the head domain or the combined neck/tail domains are either identical or very similar. For class II myosins, very similar phylogenetic trees are obtained for the head, neck, and tail domains of 47 heavy chains and for 29 essential light chains and 19 regulatory light chains. These data strongly suggest that the head, neck, and tail domains of all myosin heavy chains, and light chains at least of class II myosins, have coevolved and are likely to be functionally interdependent, consistent with biochemical evidence showing that regulated actin-dependent MgATPase activity of Dictyostelium myosin II requires isoform specific interactions between the heavy chain head and tail and light chains.